TAHYI’AH AL-BI’AH AL-LUGHAWIYYAH LIL MUSTAWA AL-JAMI’I FI DLOU’I NADHARIYYAH AL-BINYAWIYYAH AS-SULUKIYYAH - Fitriani Fitriani (Arabic Education Program IAIN Pekalongan, 2016)
One of language learning issues in any educational institutions is lack of establishmentof the language environment. In fact, based on the theories of second language learningcalled behaviorism and structuralism theory, language is a skill which takes continuouspractice and habituation. It means that the most important factor which influences thesuccess of language learning including Arabic language is the availability of goodlanguage environment. Therefore, it is necessary for the Arabic education program toestablish an Arabic language environment to support the students in improving theirlanguage skills.